SLEEP QUALITY ASSOCIATED WITH OBESITY TO ELEMENTARY SCHOOL CHILDREN IN YOGYAKARTA - Marfuah, Dewi (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
The prevalence of obesity in Indonesia is expected to increase each year. Many factors contribute to obesity, one of which is quality of sleep. Poor sleep quality lead to increased energy intake and increased sedentary lifestyle that will have an impact on obesity on children. The purpose: to examine whether poor sleep quality are risk factors of obesity in elementary school children in Yogyakarta. A case control study was conducted in 2013. A random sample of 244 obese and 244 grade-matched non obese elementary school students were selected form a cross-sectional survey previously done in the city of Yogyakarta and Bantul regency. Information of sleep quality was collected using sleep self report questionnaires. Sedentary lifestyleÂ  was collected using recall of physical activity during the last week. Nutrient intakes were collected using a food frequency questionnaires. The results showed there was a significant relationship between sleep of quality and obesity, poor sleep quality was 2,28 times more likely to be obese than good sleep quality. After controlled intake energy, gender, and sedentary lifestyle, than children with low quality of sleep was 1.9 (OR = 1.88, 95% CI: 0.95 to 3.71) times more likely to be obese than children with good quality of sleep. However, the association was not statistically significant. The conclusions of this study, poor sleep quality was associatied with increased odds of being obese in elementary school children. Keywords: sleep quality, obesity, elementary school children.